Auditor Performance from a Big Four Public Accounting Firm in Jakarta, Indonesia - Pratiwi, Monica Weni (AIBPM Publisher, 2022)
The purpose of this study is to analyze the effect of accountability and independence moderated by professional ethics on auditor performance at the Big Four public accounting firm in Jakarta, Indonesia. There are also differences in results from previous studies, which motivates the research. The respondents to this study were all auditors at the Big Four public accounting firms in Jakarta, Indonesia. The sample in this study was determined using the probability sampling method, which employs simple random sampling. The data collection technique in this study used an electronic-based questionnaire, which was then delivered using a snowball sampling technique to a sample of 100 respondents. The analytical tool used in this research is multiple linear regression analysis. The results of this study prove that accountability and independence affect professional ethics, and professional ethics affect auditor performance. Based on the results of the study, it appears that the accountability and independence of auditors at the Big Four public accounting firms in Jakarta, Indonesia, have been carried out well. Researchers suggest the Big Four public accounting firms in Jakarta, Indonesia, maintain auditor accountability and independence so that the professional ethics of an auditor remain good and can produce maximum performance.Keywords: Auditor Accountability, Auditor Performance, Auditor Independence, Auditor Professional Ethics, and Big Four Public Accounting Firm.